Solução nutritiva para o melão Gália cultivado em fibra de coco sob condições protegidas - Cosme, Christiano Rebouças (Brasil, 2016)
In recent years it has increased the cultivation of net melons of Galia type, which present an enhanced visual appearance and great flavor. With the advancement of cultivation techniques, coupled with increasing demand for quality vegetables all year round, It has invested in farming alternatives, such as hydroponics which is a technology for growing plants in nutrient solution, with or without the use of substrate, in a protected environment, allowing the planting of the same species all year, and more efficient use of water and fertilizers. However, information on the nutrient solutions are still widespread, with the need for studies adapted to local conditions and the wide range of existing cultivars. The objective of this work was to study the behavior of Galia melon (Hybrid ‘Babilônia RZ F1) grown in coconut fiber and irrigated with nutrient solutions of different concentratations. The design was a randomized blocks, with five replications and five treatments, which correspond to different macronutrients in the nutrient solution, based on the recommended solution for Furlani et al. (1999), which was considered 100% concentration (C1). Getting other treatments so determined: C2=75%; C3=50%; C4=25% e C5=12,5%. From 15 days after transplanting , the analyzes of growth and nutrient absorption were performed by collecting plants from each plot , in periods of 15, 30 , 45 and 60 days after transplanting. The concentration C3 (50%) provided higher dry matter production of shoots as well as leaf area for the muskmelon. The shoot absolute growth rate showed different trends for concentrations, however C3 (50%) concentration showed the best results. The relative growth rate of shoot and the net assimilation of shoot rate tended to decrease with time for all concentrations. The nutrient uptake by following order, K > N > P, independely of the concentration of the nutrient solution, however, the concentration of C1 (100%) showed the highest levels of N, P and K in the leaves. Considering the productivity, the highest yield was obtained at a concentration of 47% of macronutrients in the nutrient solution
Nutrient solution for Galia melon grown in coconut fiber under protected conditions
Keywords: Cucumis melo L; Cultivo sem solo; Substrato; Cucumis melo L; Soilless cultivation; Substrate; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO